2013 27th Brazilian Symposium on Software Engineering 2013
DOI: 10.1109/sbes.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of Code Anomalies Based on Architecture Sensitiveness

Abstract: Code anomalies are symptoms of software maintainability problems, particularly harmful when contributing to architectural degradation. Despite the existence of many automated techniques for code anomaly detection, identifying the code anomalies that are more likely to cause architecture problems remains a challenging task. Even when there is tool support for detecting code anomalies, developers often invest a considerable amount of time refactoring those that are not related to architectural problems. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…The techniques have focused on different methods such as a severity-based technique where code smells with higher severity are given higher priority [11]- [13], a context-based technique where code smells are prioritized according to the specific contexts of developers [14], or by using combinations of multiple factors to prioritize code smells [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…The techniques have focused on different methods such as a severity-based technique where code smells with higher severity are given higher priority [11]- [13], a context-based technique where code smells are prioritized according to the specific contexts of developers [14], or by using combinations of multiple factors to prioritize code smells [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned need for agglomeration prioritization shows that the time and effort required to identify design problems is a key factor for developers; thus, prioritization should be taken into consideration. As a matter of fact, the prioritization of smelly code has been the focus of recent research [38][39][40]. The work of Vidal et al [40], for example, proposed and assessed a set of criteria for prioritizing smell agglomerations.…”
Section: How To Improve Design Problem Identification?mentioning
confidence: 99%
“…In [1,4,6], the authors report on the relevance of code anomalies for the identification of architectural problems. As main findings, they observed that single anomalies alone do not suffice to assist developers in revealing architectural problems.…”
Section: Related Workmentioning
confidence: 99%
“…architectural problems. However, well-known anomalies in the source code (also known as code smells [2]) only provide partial hints of the location of architecture problems in a system [1,6] (Section 2).…”
Section: Introductionmentioning
confidence: 99%